Funções parentais desempenhada por madrastas e a coparentalidade do novo casal - Scremin, Ana Luiza Xavier (2020)
Divorce is one of the changes in the family's life cycle that most changes daily, increasing the complexity of family relationships. It characterizes the end of a relationship that did not work, but it also allows these couples to seek a new loving relationship, thus characterizing a remarriage. This is a new way of starting a family, since most couples who divorce have children and adolescents. When there are children in a remarriage, a new figure, called stepmother, is inserted. Unlike in the past, where the stepmother entered the family as a substitute for the maternal figure through the husband's widowhood, today, mothers and stepmothers coexist in the same family system, they can even coexist and share tasks in relation to stepchildren. As for the stepmother, when cohabiting with the children, she can take on some parental care, arising from the daily needs in relation to her stepchildren. The present study is a Collective Case Study, carried out with three families, composed of stepmother, father and at least one child at the time of cohabitation with the stepmother, which aimed to understand the experience of stepmothers in relation to parental functions and coparenting with the father of children or teenagers. For this, semi-structured interviews were conducted adapted to each family member and carried out individually with each participant. Two drawings were proposed for children and adolescents; the first, that of his family and the second in a moment with his stepmother. This dissertation is divided into two sections, the first containing a brief review of the literature, addressing the subject studied, with the method adopted and the characteristics of the participants, to provide a better understanding of the theme and the cases studied. The second section is divided into two articles with a discussion of the data obtained in conducting the research. Lastly, the final considerations of the dissertation, the references used and the appendices. It was concluded that stepmothers, when assuming responsibilities in relation to their stepchildren, sharing with father the tasks of education and care, reinforce the family bond, feeling part of a “normal family” with love, affection and some conflicts arising from the coexistence and intimacy.